Dual-coated ternary positive electrode material as well as preparation method and application thereof
Through double cladding technology, combined with dry method and spray cladding method, the double cladding layer is formed, which solves the problem of structural damage of the ternary positive electrode material during charging and discharging, and achieves high capacity and good cycle performance.
Patent Information
- Application Number
- CN202510102758.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
AI Technical Summary
The structural damage caused by the layered structure instability, mechanical instability and oxygen precipitation during the charging and discharging process of existing ternary positive electrode materials affects their capacity and cycle life.
Using double cladding technology, the island-like cladding is first formed by dry cladding, and then a uniform cladding layer is formed by spray cladding. The two work together to form a double cladding layer to avoid performance degradation caused by side reactions.
The excellent discharge specific capacity, first efficiency and cycle retention rate of the ternary positive electrode material are achieved, and the capacity and cycle performance are improved.
Smart Images

Figure CN119852377A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a double-coated ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] Ternary lithium-ion batteries are considered to be the main force and future of automotive batteries due to their excellent energy density. Nickel-cobalt-manganese ternary cathode materials have become one of the main development directions of ternary cathode materials due to their high theoretical specific capacity. Traditional polycrystalline ternary materials are composed of micron-sized secondary particles (about 1 to 30 μm) composed of densely arranged submicron-sized primary particles (about 50 to 300 nm). However, the capacity and cycle life of polycrystalline ternary cathode materials are challenged by the instability of the layered structure caused by reactions and phase changes during charge and discharge, the mechanical instability between and within the primary particle crystals, and the structural damage caused by oxygen precipitation. The nickel-cobalt-manganese ternary cathode materials with low cobalt content are more affected due to the lack of the stabilizing effect of cobalt.
[0003] Some functional doping materials and coating materials can improve the above problems to increase capacity and cycle life. For example, transition metals are added for coating, but the traditional dry coating has the defect of uneven coating; although the material distribution obtained by spray coating is more uniform than that of dry coating, the solution used for spray drying is in contact with the direct positive electrode material for a long time, which will cause lithium-hydrogen exchange reaction, resulting in phase change of the surface crystal structure and the generation of byproducts such as residual alkali on the surface, resulting in a decrease in battery capacity. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects in the prior art, thereby providing a double-coated ternary positive electrode material and a preparation method and application thereof.
[0005] To this end, the present invention provides the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a double-coated ternary positive electrode material, wherein the preparation method comprises the following steps:
[0007] S1, preparing sintering material;
[0008] S2, mixing the sintering material and the coating agent and performing dry coating to obtain a blended powder, spray coating the blended powder to obtain a coating material, and performing a second sintering to obtain a double-coated ternary positive electrode material.
[0009] According to the present invention, the coating agent includes a first metal oxide and / or a first metal hydroxide.
[0010] According to the present invention, the first metal oxide includes at least one of aluminum oxide, tungsten oxide, titanium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide and tantalum oxide.
[0011] According to the present invention, the first metal hydroxide includes at least one of cobalt hydroxide, aluminum hydroxide and zirconium hydroxide.
[0012] According to the present invention, based on the mass of the sintering material, the mass of the coating agent is 0.2-1 wt%.
[0013] According to the present invention, the rotation speed of the dry coating is 3000-4000 rpm and the time is 15-30 min.
[0014] According to the present invention, the spray coating comprises the following steps: dissolving a water-soluble metal salt and / or boric acid in water to obtain a spray coating solution, and spraying the spray coating solution on the blending powder.
[0015] According to the present invention, the concentration of the water-soluble metal salt and / or boric acid in the spray coating solution is 2-10 wt%.
[0016] According to the present invention, the water-soluble metal salt includes at least one of lactate, carbonate, nitrate and tungstate; optionally, the water-soluble metal salt includes at least one of aluminum lactate, manganese lactate, cobalt lactate, ammonium zirconium carbonate, aluminum nitrate, cobalt nitrate, manganese nitrate, zirconium nitrate, antimony nitrate, ammonium tungstate and lithium tungstate.
[0017] According to the present invention, the mass ratio of the blending powder to the spray coating solution is 100:(5-15).
[0018] According to the present invention, the conditions for the spray coating are: the spray coating temperature is 5-40°C, the single spraying time is 5-120s, and the number of sprayings is 2-30 times; optionally, the spray coating temperature is 10-30°C, the single spraying time is 10-60s, and the number of sprayings is 5-15 times.
[0019] In the present invention, the mass ratio here is the ratio of the mass of the blending powder to the total mass of the spray coating solution sprayed multiple times after spraying the spray coating solution. Typically, but not limiting, the mass ratio of the blending powder to the spray coating solution is 100:10, and the number of spraying is 10 times, wherein the mass ratio of the blending powder to the spray coating solution in a single spraying can be 100:1 or 100:15, as long as the mass ratio of the blending powder to the spray coating solution is 100:10 after 10 sprayings.
[0020] According to the present invention, the temperature of the second sintering is 400-650° C. and the time is 4-10 hours.
[0021] In the present invention, the second sintering is performed in an air environment.
[0022] According to the present invention, the method for preparing the sintering material comprises the following steps: mixing a lithium source, a ternary positive electrode precursor, and a metal additive and performing a first sintering to obtain a sintering material.
[0023] In the present invention, the product obtained after the first sintering is further subjected to crushing, pulverizing and sieving treatments.
[0024] According to the present invention, the structural formula of the ternary cathode precursor is Ni x Co y Mn z (OH)2, wherein 0.90≤x≤0.98, 0.01≤y≤0.08, 0.01≤z≤0.05, x+y+z=1.
[0025] According to the present invention, the average particle size of the ternary positive electrode precursor is 1-15 μm, and can be optionally 2-5 μm.
[0026] In the present invention, the lithium source includes a water-soluble lithium salt; optionally, the lithium source includes at least one of lithium hydroxide monohydrate, anhydrous lithium hydroxide, and lithium carbonate.
[0027] According to the present invention, the metal additive includes a second metal oxide and / or a second metal hydroxide.
[0028] According to the present invention, the second metal oxide includes at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, tantalum oxide and tungsten oxide.
[0029] According to the present invention, the second metal hydroxide includes at least one of aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, strontium hydroxide and yttrium hydroxide.
[0030] In the present invention, the vanadium oxide includes at least one of vanadium pentoxide (V2O5), vanadium dioxide (VO2) and vanadium trioxide (V2O3).
[0031] According to the present invention, the molar ratio of the sum of the metal elements in the ternary positive electrode precursor to the lithium element in the lithium source is 1:1.02-1.08.
[0032] According to the present invention, based on the mass of the ternary positive electrode precursor, the mass of the metal additive is 0.5-1.5wt%.
[0033] According to the present invention, the temperature of the first sintering is 600-900° C., and the time is 6-20 hours; optionally, the temperature of the first sintering is 750-850° C., and the time is 8-15 hours.
[0034] In the present invention, the first sintering is performed in an oxygen environment.
[0035] The second aspect of the present invention protects a double-coated ternary positive electrode material prepared by the aforementioned preparation method.
[0036] A third aspect of the present invention protects a secondary battery, wherein the secondary battery comprises the aforementioned double-coated ternary positive electrode material.
[0037] Preparation method of battery: adding positive electrode material, carbon black and PVDF in a mass ratio of 90:5:5, adding N-methylpyrrolidone, wherein the mass ratio of N-methylpyrrolidone to PVDF is 10-15:1, as a dispersant, preparing positive electrode slurry, placing it in a centrifuge for centrifugation for 15-30 minutes, and evenly coating the positive electrode slurry on the carbon-coated aluminum foil, with a coating amount of 4-6 mg / cm 2 , place the carbon-coated aluminum foil in an oven and dry it at 100-120°C for 2-3 hours to obtain a dried electrode sheet; roll the dried electrode sheet with a roller press at 40kN, place it in an oven again, and dry it at 100-120°C for 2-3 hours, and finally use a corresponding size mold to press and cut to obtain a positive electrode sheet; in an argon atmosphere of a glove box, use a Celgard 2500 diaphragm, a lithium metal sheet as a negative electrode sheet, and an LBC3021C011 electrolyte to assemble a battery in the order of negative electrode sheet, electrolyte, diaphragm, electrolyte, and positive electrode sheet.
[0038] The technical solution of the present invention has the following advantages:
[0039] 1. The present invention provides a preparation method of a double-coated ternary positive electrode material, wherein the preparation method comprises the following steps: S1, preparing a sintering material; S2, mixing the sintering material and a coating agent for dry coating to obtain a blended powder, spray coating the blended powder to obtain a coating material, and performing a second sintering to obtain a double-coated ternary positive electrode material; in the present invention, the sintering material is first dry-coated to obtain a blended powder and then spray-coated, and the dry coating can consume a large amount of by-products such as residual alkali on the surface of the sintering material and form a large number of relatively obvious island-shaped coatings; wet coating can form a uniformly dispersed coating layer, and the two act synergistically to form a double coating layer and avoid performance degradation caused by side reactions; and compared with wet coating such as coprecipitation method, spray coating avoids the long-term contact between the ternary positive electrode precursor and water, resulting in side reactions caused by lithium-hydrogen exchange reactions, so that the obtained double-coated ternary positive electrode material has excellent discharge specific capacity, first efficiency and cycle retention rate.
[0040] 2. The specific type of coating agent in the present invention can further improve the coating effect, thereby improving the capacity and cycle performance.
[0041] 3. The specific types of water-soluble metal salts in the present invention can further reduce the amount of Cl required in conventional wet coating. - 、SO4 2- The introduction of impurity ions such as ions brings about better coating effects.
[0042] 4. The specific conditions of the spray coating in the present invention can further improve the dispersion uniformity of the water-soluble metal salt, resulting in a more uniform and better coating effect.
[0043] 5. The specific conditions of the first sintering in the present invention can further ensure the appropriate crystal size and consistency of the crystal size of the positive electrode material, resulting in excellent capacity and cycle performance.
[0044] 6. The specific average particle size of the ternary positive electrode precursor in the present invention can further increase the exposed dominant crystal plane of the single crystal, allowing for more complete contact with the external electrolyte, resulting in higher capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 It is an electron microscope picture of the blended powder of Example 1;
[0047] Figure 2 This is an electron microscope picture of the coating material of Example 1. DETAILED DESCRIPTION
[0048] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0049] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0050] Example 1
[0051] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0052] S1, 600.00 g (6.5 mol) of Ni with an average particle size of 3.5 μm 0.92 Co 0.06 Mn 0.02 (OH)2 ternary precursor, 281.57g (6.7mol) lithium hydroxide monohydrate, 3.648g aluminum hydroxide, and 1.705g zirconium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered for the first time in an oxygen atmosphere at a sintering temperature of 800°C for 10h, and then crushed, pulverized, and sieved to obtain a sintered material;
[0053] S2, collect 600g of the sintered material prepared in step S1 and 3g of cobalt hydroxide, put them into a high-speed mixer and mix them for dry coating, the dry coating speed is 3500rpm, the time is 20min, and a blended powder is obtained; 3g of ammonium zirconium carbonate is mixed with 60mL of water to obtain a spray coating solution, wherein the concentration of ammonium zirconium carbonate is 4.8wt%; spray the spray coating solution on the blended powder, and the electron microscope picture is as shown Figure 1 As shown, from Figure 1 It can be seen that there is obvious island coating; the temperature of spray coating is 20℃, the time of single spraying is 30s, and the number of spraying is 10 times; the mass ratio of blending powder to spray coating solution is 100:1, and the coating material is obtained; the electron microscope picture is as follows Figure 2 As shown, from Figure 2 It can be seen that the coating layer is relatively uniform; the coating material is placed in a muffle furnace and subjected to a second sintering in an air atmosphere at a sintering temperature of 550°C and a sintering time of 7 hours. After that, it is crushed and sieved to obtain a double-coated ternary positive electrode material.
[0054] Example 2
[0055] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0056] S1, 601.51g (6.5mol) of Ni with an average particle size of 2μm 0.94 Co 0.01 Mn 0.05 (OH)2 ternary precursor, 167.65g (7.0mol) anhydrous lithium hydroxide, 1.8g tungsten oxide, and 1.2g zirconium hydroxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered for the first time in an oxygen atmosphere at a sintering temperature of 850°C for 8h, and then crushed, pulverized, and sieved to obtain a sintering material;
[0057] S2, collect 600g of the sintered material prepared in step S1 and 6g of alumina, put them into a high-speed mixer and mix them for dry coating, the dry coating speed is 3000rpm, the time is 15min, and a blending powder is obtained; 6g of cobalt nitrate is evenly mixed with 60mL of water to obtain a spray coating solution, wherein the concentration of cobalt nitrate is 9wt%; spray the spray coating solution on the blending powder, the spray coating temperature is 30°C, the single spraying time is 10s, and the number of sprayings is 15 times; the mass ratio of the blending powder to the spray coating solution is 100:2, and a coating material is obtained; the coating material is placed in a muffle furnace, and a second sintering is carried out in an air atmosphere, the sintering temperature is 650°C, and the sintering time is 4h, and then the double-coated ternary positive electrode material is obtained by crushing and sieving.
[0058] Example 3
[0059] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0060] The method of Example 1 is followed, except that "3.648 g aluminum hydroxide, 1.705 g zirconium oxide" is replaced with "5.353 g strontium oxide".
[0061] Example 4
[0062] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0063] The method of Example 1 is followed, except that “3 g of ammonium zirconium carbonate is uniformly mixed with 60 mL of water to obtain a spray coating solution, wherein the concentration of ammonium zirconium carbonate is 4.8 wt%” is changed to “1.5 g of aluminum lactate and 1.5 g of lithium tungstate are uniformly mixed with 60 mL of water to obtain a spray coating solution, wherein the concentration of aluminum lactate is 2.4 wt% and the concentration of lithium tungstate is 2.4 wt%”.
[0064] Example 5
[0065] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0066] The method of Example 1 is the same, except that the spray coating temperature is 10° C., the single spraying time is 80 s, and the number of spraying is 20 times.
[0067] Example 6
[0068] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0069] The method of Example 1 is the same, except that the first sintering is performed at a sintering temperature of 900° C. and a sintering time of 20 h.
[0070] Example 7
[0071] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0072] The method of Example 1 is the same as that of Example 1, except that the average particle size of Ni is 3.5 μm. 0.92 Co 0.06 Mn 0.02 (OH)2" was changed to "Ni with an average particle size of 5 μm 0.92 Co 0.06 Mn 0.02 (OH)2”.
[0073] Example 8
[0074] This embodiment provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0075] The method of Example 1 is the same, except that in S2, "3 g of cobalt hydroxide" is changed to "1.5 g of aluminum hydroxide and 1.5 g of tungsten oxide".
[0076] Comparative Example 1
[0077] This comparative example provides a method for preparing a coated ternary positive electrode material, and the specific steps include:
[0078] S1, 600.00 g (6.5 mol) of Ni with an average particle size of 3.5 μm 0.92 Co 0.06 Mn 0.02 (OH)2 ternary precursor, 281.57g (6.7mol) lithium hydroxide monohydrate, 3.648g aluminum hydroxide, and 1.705g zirconium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered for the first time in an oxygen atmosphere at a sintering temperature of 800°C for 10h, and then crushed, pulverized, and sieved to obtain a sintered material;
[0079] S2, collect 600g of the sintered material prepared in step S1 and 3g of cobalt hydroxide, put them into a high-speed mixer and mix them for dry coating. The dry coating speed is 3500rpm and the time is 20min to obtain a blended powder. The blended powder is placed in a muffle furnace and subjected to a second sintering in an air atmosphere. The sintering temperature is 550°C and the sintering time is 7h. After that, the coated ternary positive electrode material is obtained by crushing and sieving.
[0080] Comparative Example 2
[0081] This comparative example provides a method for preparing a coated ternary positive electrode material, and the specific steps include:
[0082] S1, 600.00 g (6.5 mol) of Ni with an average particle size of 3.5 μm 0.92 Co 0.06 Mn 0.02 (OH)2 ternary precursor, 281.57g (6.7mol) lithium hydroxide monohydrate, 3.648g aluminum hydroxide, and 1.705g zirconium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered for the first time in an oxygen atmosphere at a sintering temperature of 800°C for 10h, and then crushed, pulverized, and sieved to obtain a sintered material;
[0083] S2, collecting 600g of the sintered material prepared in step S1, and evenly mixing 3g of ammonium zirconium carbonate with 60mL of water to obtain a spray coating solution, wherein the concentration of ammonium zirconium carbonate is 5wt%; spraying the spray coating solution on the sintered material, the spray coating temperature is 20°C, the single spraying time is 30s, and the number of spraying is 10 times; the mass ratio of the sintered material to the spray coating solution is 100:1, and a coating material is obtained; placing the coating material in a muffle furnace, and performing a second sintering in an air atmosphere, the sintering temperature is 550°C, and the sintering time is 7h, and then crushing and sieving to obtain a coated ternary positive electrode material.
[0084] Comparative Example 3
[0085] This comparative example provides a method for preparing a coated ternary positive electrode material, and the specific steps include:
[0086] S1, 601.51g (6.5mol) of Ni with an average particle size of 2μm 0.94 Co 0.01 Mn 0.05 (OH)2 ternary precursor, 167.65g (7.0mol) anhydrous lithium hydroxide, 1.8g tungsten oxide, and 1.2g zirconium hydroxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered for the first time in an oxygen atmosphere at a sintering temperature of 850°C for 8h, and then crushed, pulverized, and sieved to obtain a sintering material;
[0087] S2, collect 600g of the sintered material prepared in step S1 and 6g of alumina, put them into a high-speed mixer and mix them for dry coating. The dry coating speed is 3000rpm and the time is 15min to obtain a blended powder; place the blended powder in a muffle furnace and perform a second sintering in an air atmosphere. The sintering temperature is 650°C and the sintering time is 4h. Then, the double-coated ternary positive electrode material is obtained by crushing and sieving.
[0088] Comparative Example 4
[0089] This comparative example provides a method for preparing a double-coated ternary positive electrode material, and the specific steps include:
[0090] S1, 600.00 g (6.5 mol) of Ni with an average particle size of 3.5 μm 0.92 Co 0.06 Mn 0.02 (OH)2 ternary precursor, 281.57g (6.7mol) lithium hydroxide monohydrate, 3.648g aluminum hydroxide, and 1.705g zirconium oxide were mixed in a high-speed mixer, placed in a muffle furnace, and sintered for the first time in an oxygen atmosphere at a sintering temperature of 800°C for 10h, and then crushed, pulverized, and sieved to obtain a sintered material;
[0091] S2, collect 600g of the sintered material prepared in step S1 and 3g of cobalt hydroxide, put them into a high-speed mixer and mix them for dry coating, the dry coating speed is 3500rpm, the time is 20min, and a blending powder is obtained; 21g of ferrous sulfate heptahydrate, 8.6g of ammonium dihydrogen phosphate, 31g of citric acid monohydrate and 600mL of water are mixed evenly, the pH is adjusted to 10 with ammonia water, heated to 40°C and continuously stirred to obtain a gel; the positive electrode material is added to the gel, ultrasonically mixed for 10min, and then centrifuged at 3000rpm for 5min; the mass ratio of the blending powder to the gel is 1:1, and the coating material is obtained after filtering and drying; the coating material is placed in a muffle furnace and a second sintering is carried out in a nitrogen atmosphere, the sintering temperature is 550°C, and the sintering time is 7h, and then the double-coated ternary positive electrode material is obtained by crushing and sieving.
[0092] Test Case
[0093] Preparation method of battery: adding positive electrode material, carbon black and PVDF in a mass ratio of 90:5:5, adding N-methylpyrrolidone, wherein the mass ratio of N-methylpyrrolidone to PVDF is 10:1, as a dispersant, preparing positive electrode slurry, placing it in a centrifuge for 30 minutes, and evenly coating the positive electrode slurry on the carbon-coated aluminum foil, with a coating amount of 5 mg / cm 2 , place the carbon-coated aluminum foil in an oven and dry it at 100°C for 2 hours to obtain a dried electrode sheet; use a roller press to roll the dried electrode sheet at 40 kN, place it in an oven and dry it at 100°C for 2 hours, and finally use a corresponding size mold to press and cut to obtain a positive electrode sheet; in an argon atmosphere in a glove box, use a Celgard 2500 diaphragm, a lithium metal sheet as a negative electrode sheet, and an LBC3021C011 electrolyte to assemble a battery in the order of negative electrode sheet, electrolyte, diaphragm, electrolyte, and positive electrode sheet.
[0094] Then at 25°C, charge to 4.25V at a rate of 0.2C, and then discharge to 2.8V at a rate of 0.2C. This is a cycle process. The discharge capacity this time is the first discharge specific capacity, and the first efficiency is the first discharge specific capacity / first charge specific capacity × 100%.
[0095] It is charged to 4.25V at a rate of 0.5C and discharged to 2.8V at a rate of 1C. The discharge capacity at a rate of 1C in the first cycle is the 1C specific capacity.
[0096] Charge to 4.25V at a rate of 0.2C, then discharge to 2.8V at a rate of 0.2C. After 2 cycles, charge to 4.25V at a rate of 0.5C, discharge to 2.8V at a rate of 1C, cycle 50 cycles, record the charge and discharge capacity of the 3rd cycle and the charge and discharge capacity of the 52nd cycle, cycle retention rate = 52nd cycle discharge capacity / 3rd cycle discharge capacity × 100%; see Table 1 for specific test results.
[0097] Table 1
[0098]
[0099]
[0100] By comparing the embodiment with comparative examples 1-4, it can be seen that the sintered material is dry-coated to obtain a blended powder and then spray-coated. The dry coating can consume a large amount of by-products on the surface of the positive electrode material such as residual alkali and form a large number of relatively obvious island coatings. The wet coating can form a dispersed and uniform coating layer. The two work synergistically to form a double coating layer and avoid performance degradation caused by side reactions. Compared with wet coating such as co-precipitation, spray coating avoids long-term contact between the ternary positive electrode precursor and water, which leads to side reactions caused by lithium-hydrogen exchange reactions, so that the obtained double-coated ternary positive electrode material has excellent discharge specific capacity, initial efficiency and cycle retention rate.
[0101] Comparison between Example 1 and Example 3 shows that specific types of coating agents can further improve the coating effect, thereby improving capacity and cycle performance.
[0102] Comparison between Example 1 and Example 4 shows that specific types of water-soluble metal salts can further reduce the amount of Cl required in conventional wet coating. - 、SO4 2- The introduction of impurity ions such as ions brings about better coating effects.
[0103] Comparing Example 1 with Example 5, it can be seen that the specific conditions of spray coating can further improve the dispersion uniformity of the water-soluble metal salt, resulting in a more uniform and better coating effect.
[0104] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a double-coated ternary positive electrode material, characterized in that: The preparation method comprises the following steps: S1, preparing sintering material; S2, mixing the sintering material and the coating agent and performing dry coating to obtain a blended powder, spray coating the blended powder to obtain a coating material, and performing a second sintering to obtain a double-coated ternary positive electrode material.
2. The preparation method according to claim 1, characterized in that: The coating agent includes a first metal oxide and / or a first metal hydroxide; Optionally, the first metal oxide includes at least one of aluminum oxide, tungsten oxide, titanium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, and tantalum oxide; Optionally, the first metal hydroxide includes at least one of cobalt hydroxide, aluminum hydroxide, and zirconium hydroxide; and / or, based on the mass of the sintered material, the mass of the coating agent is 0.2-1wt%; And / or, the rotation speed of the dry coating is 3000-4000 rpm, and the time is 15-30 min.
3. The preparation method according to claim 1 or 2, characterized in that: The spray coating comprises the following steps: dissolving a water-soluble metal salt and / or boric acid in water to obtain a spray coating solution, and spraying the spray coating solution on the blending powder; Optionally, the concentration of the water-soluble metal salt and / or boric acid in the spray coating solution is 2-10 wt %; Optionally, the water-soluble metal salt includes at least one of lactate, carbonate, nitrate, and tungstate; Optionally, the water-soluble metal salt includes at least one of aluminum lactate, manganese lactate, cobalt lactate, ammonium zirconium carbonate, aluminum nitrate, cobalt nitrate, manganese nitrate, zirconium nitrate, antimony nitrate, ammonium tungstate, and lithium tungstate; Optionally, the mass ratio of the blending powder to the spray coating solution is 100:(5-15).
4. The preparation method according to any one of claims 1 to 3, characterized in that: The spray coating conditions are as follows: the spray coating temperature is 5-40°C, the single spraying time is 5-120s, and the number of sprayings is 2-30 times; Optionally, the temperature of the spray coating is 10-30° C., the time of a single spraying is 10-60 s, and the number of sprayings is 5-15 times.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The second sintering is carried out at a temperature of 400-650° C. and for a time of 4-10 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The sintering material preparation method comprises the following steps: mixing a lithium source, a ternary positive electrode precursor, and a metal additive and performing a first sintering to obtain a sintering material; Optionally, the structural formula of the ternary cathode precursor is Ni x Co y Mn z (OH)2, wherein 0.90≤x≤0.98, 0.01≤y≤0.08, 0.01≤z≤0.05, x+y+z=1; And / or, the average particle size of the ternary cathode precursor is 1-15 μm, optionally 2-5 μm; and / or, the metal additive comprises a second metal oxide and / or a second metal hydroxide; Optionally, the second metal oxide includes at least one of magnesium oxide, aluminum oxide, titanium oxide, vanadium oxide, gallium oxide, strontium oxide, yttrium oxide, zirconium oxide, niobium oxide, molybdenum oxide, antimony oxide, lanthanum oxide, tantalum oxide, and tungsten oxide; Optionally, the second metal hydroxide includes at least one of aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, strontium hydroxide, and yttrium hydroxide.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the sum of the metal elements in the ternary positive electrode precursor to the lithium element in the lithium source is 1:1.02-1.08; And / or, based on the mass of the ternary positive electrode precursor, the mass of the metal additive is 0.5-1.5wt%.
8. The preparation method according to claim 6, characterized in that: The first sintering temperature is 600-900° C., and the time is 6-20 hours; optionally, the first sintering temperature is 750-850° C., and the time is 8-15 hours.
9. A double-coated ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the double-coated ternary positive electrode material according to claim 9.
Citation Information
Patent Citations
Preparation method for composite coated-type ternary material
CN105514377A
Preparation method of Ni-Co-Mn hydroxide precursor, Ni-Co-Mn hydroxide precursor and application
CN107507970A
Preparation method of high-nickel ternary material, high-nickel ternary material and battery
CN109524659A
Cobalt-free nickel-manganese positive electrode material and preparation method and application thereof
CN113161548A
High-nickel ternary lithium ion battery positive electrode material and production method thereof
CN113328072A